Hybrid Identities and Power Dynamics in Postcolonial Umuofia: A Close Reading of The Voter - Stefanus Galang Ardana (k@ta: A Biannual Publication on the Study of Language and Literature, 2025)
Chinua Achebe’s short story The Voter examines the idea of compromised agency in postcolonial Nigeria through the character of Rufus Okeke (Roof). Through the lens of Homi Bhabha’s ideas of mimicry and hybridity, this paper reads Roof’s dilemma while also revealing the limitations of Bhabha. Bhabha’s concept of hybrid and the third space are sites of possible negotiation and resistance. Meanwhile Roof’s engagement with a corrupt political system illustrates a cruel world of psychological tension, economic need, and moral compromise. His choices may not be acts of liberation themselves; rather, they are strategies for survival within a structure that continues to reflect colonial relations of power. This study juxtaposes Bhabha’s theory with Frantz Fanon’s and Achille Mbembe’s materialist critiques. This demonstrates how Achebe advocates for a postcolonial reading that takes the lived realities of complicity and survival more seriously. Moreover, the paper argues for a more grounded view of how identity is negotiated under the shadow of colonial rule.